An investigation of highly accurate and precise robotic hole measurements using non‐contact devices - Zahid Usman; Radmehr Monfared; Niels Lohse; Michael Jackson (2016)
Industrial robots arms are widely used in manufacturing industry because of their support for automation. However, in metrology, robots have had limited application due to their insufficient accuracy. Even using error compensation and calibration methods, robots are not effective for micrometre (μm) level metrology. Non‐contact measurement devices can potentially enable the use of robots for highly accurate metrology. However, the use of such devices on robots has not been investigated. The research work reported in this paper explores the use of different non‐contact measurement devices on an industrial robot. The aim is to experimentally investigate the effects of robot movements on the accuracy and precision of measurements. The focus has been on assessing the ability to accurately measure various geometric and surface parameters of holes despite the inherent inaccuracies of industrial robot. This involves the measurement of diameter, roundness and surface roughness. The study also includes scanning of holes for measuring internal features such as start and end point of a taper. Two different non‐contact measurement devices based on different technologies are investigated. Furthermore, effects of eccentricity, vibrations and thermal variations are also assessed. The research contributes towards the use of robots for highly accurate and precise robotic metrology.